Clinical Characteristic of Headache among Medical Students Experienced Online Learning in University during the Pandemic - Febriza, Ami; Yusbar, Yushusna; Sompa, Andi Weri (Smart Medical Journal, 2023)
Background: The lecture used online learning as an alternative method for minimizing the spreading covid-19 during pandemic. Headache is one of the very popular complaints during the medical education process, and it happens owing many physical or psychological stressors. It reported more common in medical students, notably during this online learning methods.Aim: This study aimed to evaluate the clinical characteristics of headaches and associated factors among medical students during online learning.Methods: A cross-sectional study was conducted at the University of Muhammadiyah Makassar from November 2021 to May 2022. A total of 220 medical students who have experienced forms of headache and had headache attacks during the past 1 years were included in this study. Respondents filled out a structured questionnaire, which consisted of demographic data, associated factors during online learning, and headache characteristics. Chi-square test was used to test the difference in proportion. All statistical test were considered as significant if p-value <0.05. The data obtained was processed using SPSS 23.Results: Body posture during online learning and lecture duration had a significant relationship with headaches' location, duration, and frequency (p-value < 0.05). Body posture during online learning, duration of lectures, and frequency of lectures significantly correlate with activity exacerbated headaches (p-value < 0.05). Body posture also significantly correlates with headache severity (p-value < 0.05).Conclusions: The results show that the clinical characteristics of headache are high in medical students that experience online learning during this pandemic situation.